2022
DOI: 10.1044/2021_jslhr-21-00298
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Methodological Decisions on Assessing the Spatiotemporal Stability of Speech Movement Sequences

Abstract: Purpose: The spatiotemporal index (STI) is a widely used approach for measuring speech pattern stability across multiple repetitions of a stimulus. In this study, we examine how methodological choices in the implementation of the STI (including the number of repetitions, length of stimuli, and parsing procedure) can affect its value. Method: To evaluate how each methodological decision affects the STI, we use a synthetic data framework that allows for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We must note that our study included fewer repetitions than the original formulation of STI, which was calculated based on 15 repetitions of a single phrase [22]. Although there is not an established minimum number of repetitions that should be used when calculating STI, having more repetitions improves reliability [58]. In our analysis, STI acceleration of the tongue and LL showed a statistically significant association with intelligible speaking rate.…”
Section: Discussionmentioning
confidence: 93%
“…We must note that our study included fewer repetitions than the original formulation of STI, which was calculated based on 15 repetitions of a single phrase [22]. Although there is not an established minimum number of repetitions that should be used when calculating STI, having more repetitions improves reliability [58]. In our analysis, STI acceleration of the tongue and LL showed a statistically significant association with intelligible speaking rate.…”
Section: Discussionmentioning
confidence: 93%
“…Variability in speech production occurs at many levels, including articulator positions for different consonants (e.g., Refs. [80][81][82]), coordination between two articulators for a particular segment and even across segments (coarticulation, also referred to as coproduction), sentence-level timing (see review in [83]), and the many acoustic phonetic outputs related to segmental and prosodic characteristics of the speech signal. Many of the articulatory variabilities for vowel segments such as /u/ and the lax vowels [84] and rhotics and liquids [85,86] are in the service of acoustic stability; in this sense, these are "good" variabilities.…”
Section: Can Performance Onmentioning
confidence: 99%
“…Well-controlled articulatory movement patterns are believed to be highly consistent, whereas deviations in neuromuscular activity decreases movement stability. Although prior work has primarily attributed instability to increased demands on the motor system (e.g., task complexity, motor learning, disordered speech; McHenry, 2003;Saletta et al, 2018), it has recently been shown that in absence of behavioral changes, increased length (in syllables) in stimuli increases STI values in simulated data (Wisler et al, 2022), suggesting STI is more sensitive to temporal instability in longer stimuli. Less is known about how articulatory variability is impacted by syllable length in individuals with dysarthria due to ALS.…”
Section: Introductionmentioning
confidence: 99%